2005
DOI: 10.1111/j.1365-246x.2005.02680.x
|View full text |Cite
|
Sign up to set email alerts
|

Moment tensor inversion with single-component historical seismograms: The 1909 Benavente (Portugal) and Lambesc (France) earthquakes

Abstract: S U M M A R YMoment tensor inversion of early XX century mechanical seismograph recordings offers the opportunity to estimate source parameters for a number of important earthquakes. This knowledge is crucial for understanding regional tectonics and estimating seismic hazard; but processing of the historical seismograms is often difficult. Especially, the rotation of horizontal seismograms into radial (P-SV ) and transverse (SH) components tends to fail; for example, if one polarity is wrong, if the alignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 18 publications
3
65
1
4
Order By: Relevance
“…The epicentre location was estimated at 38.9 • N, 8.8 • W, using the available macroseismic information, by Kárník (1969). From different studies, based on the seismic moment estimation, the moment magnitude, Mw, was estimated between 6.0 and 6.2 and Ms close to 6.3 (Teves-Costa et al 1999Dineva et al 2002;Stich et al 2005). Stich et al (2005) determined a focal mechanism of a reverse faulting.…”
Section: Relocation Using the Bakun And Wentworth Methodology (1997)mentioning
confidence: 99%
See 1 more Smart Citation
“…The epicentre location was estimated at 38.9 • N, 8.8 • W, using the available macroseismic information, by Kárník (1969). From different studies, based on the seismic moment estimation, the moment magnitude, Mw, was estimated between 6.0 and 6.2 and Ms close to 6.3 (Teves-Costa et al 1999Dineva et al 2002;Stich et al 2005). Stich et al (2005) determined a focal mechanism of a reverse faulting.…”
Section: Relocation Using the Bakun And Wentworth Methodology (1997)mentioning
confidence: 99%
“…From different studies, based on the seismic moment estimation, the moment magnitude, Mw, was estimated between 6.0 and 6.2 and Ms close to 6.3 (Teves-Costa et al 1999Dineva et al 2002;Stich et al 2005). Stich et al (2005) determined a focal mechanism of a reverse faulting. This is in agreement with other focal mechanisms calculated for this region (Borges et al 2001).…”
Section: Relocation Using the Bakun And Wentworth Methodology (1997)mentioning
confidence: 99%
“…A throughout search for original records of the event showed that many of them were lost or were destroyed. Nowadays, combined efforts of Teves-Costa et al (1999, Dineva et al (2002) and Stich et al (2005) to locate records of the Benavente earthquake allowed to recover 31 potentially useful seismograms of this event (Table 1). Data sources include original smoked paper recordings and photographic contacts as well as photocopies or reproductions of seismograms in journals.…”
Section: Instrumental Seismic Records Collectionmentioning
confidence: 99%
“…Four centuries later occurred another strong earthquake in the LTV on 23 April 1909 (Mw = 6.0, estimated by Stich et al 2005). It produced large damage in several small villages located in the eastern bank of the Tagus River, as Samora Correia, Benavente and Santo Estevão (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation